Standards, Methods and Solutions of Metrology - Cocco, Luigi (IntechOpen, 2019)
The goal of acceptable quality, cost, and time is a decisive challenge in every engineering development process. To be familiar with metrology requires choosing the best combination of techniques, standards, and tools to control a project from advanced simulations to final performance measurements and periodic inspections. This book contains a cluster of chapters from international academic authors who provide a meticulous way to discover the impacts of metrology in both theoretical and application fields. The approach is to discuss the key aspects of a selection of untraditional metrological topics, covering the analysis procedures and set of solutions obtained from experimental studies.